Halving poverty by doubling aid: how well founded is the optimism of the World Bank? - Rolf J. Langhammer (Kiel Institute for World Economics (IfW), 2002)
The article criticizes the World Bank as overy optimistic concerning its ability to raise the effectiveness of aid by concentrating aid on countries with "good" policies. It is shown that aid flows to the main recipient regions yielded the highest correlation to growth when their magnitudes shrank. It is argued that more aid can impair the quality of domestic policies in the recipients (endogeneity problem). The paper instead pleads for a shift of aid policies from country-oriented to issue-oriented aid. An international endowment fund under supranational law should help to finance such issues.
Keywords: O4; O2; 330; economic growth; poverty reduction; aid effectiveness; policy orientation; `Dutch Disease' effects of aid; development aid; Entwicklungshilfe; Anpassungsprogramm des IWF; Armutspolitik; Wirtschaftspolitische Wirkungsanalyse; Dutch Disease; Entwicklungsländer